Obstructive sleep apnoea with Arnold-Chiari malformation. Issue 6 (June 1995) - Doherty, M J; Spence, D P; Young, C; Calverley, P M
Abstract : A case of obstructive sleep apnoea associated with the Arnold-Chiari malformation is described, in which the loss of pharyngeal sensation seems to have played an important part in the aetiology of the obstruction of the upper airway.